1981
DOI: 10.1084/jem.154.4.1150
|View full text |Cite
|
Sign up to set email alerts
|

Induction of monocyte procoagulant activity by murine hepatitis virus type 3 parallels disease susceptibility in mice.

Abstract: The in vitro induction of procoagulant activity (PCA) in murine peripheral blood mononuclear cells (PBM) by murine hepatitis virus type 3 (MHV-3) correlates with the disease susceptibility in three strains of mice. PBM from BALB/c mice, a strain in which MHV-3 infection results in fatal acute fulminant hepatitis, responds to the virus with a robust PCA response, whereas PBM from C3H/St mice, a strain which develops mild acute hepatitis followed by chronic hepatitis, only exhibit a modest PCA response. In contr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
120
1

Year Published

1983
1983
2009
2009

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(128 citation statements)
references
References 33 publications
7
120
1
Order By: Relevance
“…It should be noted that macrophages from A/J mice can produce FGL2 to interferon gamma in vitro, yet do not generate FGL2 to MHV-3 in vivo. [31][32][33] Taken together, the data demonstrate that production of FGL2 is tightly regulated and supports the important role of Treg-expressed FGL2 in the pathogenesis of MHV-3-induced FH. The mechanism by which FGL2 mediates its immunosuppressive activity is currently under intensive investigation.…”
Section: Discussionsupporting
confidence: 57%
“…It should be noted that macrophages from A/J mice can produce FGL2 to interferon gamma in vitro, yet do not generate FGL2 to MHV-3 in vivo. [31][32][33] Taken together, the data demonstrate that production of FGL2 is tightly regulated and supports the important role of Treg-expressed FGL2 in the pathogenesis of MHV-3-induced FH. The mechanism by which FGL2 mediates its immunosuppressive activity is currently under intensive investigation.…”
Section: Discussionsupporting
confidence: 57%
“…These proteins have been shown to exhibit coagulant and angiogenic activity, as well as immunoregulatory activity (1,2,30). Similar to other members of the fibrinogen superfamily, our laboratory has recently discovered (19) that FGL2 inhibits murine DC maturation and adaptive T cell immune responses, in addition to its role in innate immunity through its ability to activate the coagulation system (7)(8)(9)(10)(11)(12)(13)(14)(15).…”
Section: Discussionmentioning
confidence: 99%
“…FGL2 was first cloned from human CTLs, and its protein structure deduced from the nucleotide sequence showed a high degree of homology to fibrinogen ␤ and ␥ subunits (3). FGL2 has been shown to play an important role in innate immunity as an immune coagulant expressed by activated reticuloendothelial cells (macrophages and endothelial cells) (4 -6) and has been implicated in the pathogenesis of several inflammatory disorders, including viral hepatitis (7)(8)(9)(10), allo-and xenograft rejection (11)(12)(13), and cytokine induced fetal loss (14,15). In a previous report (13), we showed that Ab to FGL2 ameliorated allograft rejection.…”
mentioning
confidence: 99%
“…Accordingly, injury, infection, and (auto)immunity are associated with extravascular fibrin(ogen) (3)(4)(5)(6).…”
mentioning
confidence: 99%